Differences in medical costs among urban lung cancer patients with different health insurance schemes: a retrospective study - Yichen Li; Yong Yang; Jia Yuan; Lieyu Huang; Yong Ma; Xuefeng Shi (BMC, 2022)
Abstract Background Health insurance plays a significant role in reducing the financial burden for lung cancer patients. However, limited research exists regarding the differences in medical costs for lung cancer patients with different insurance schemes across different cities. We aimed to assess disparities in lung cancer patients' costs by insurance type and city-specific insurance type. Methods Claim data of China Urban Employees' Basic Medical Insurance (UEBMI) and Urban Residents' Basic Medical Insurance (URBMI) between 2010 and 2016 were employed to investigate differences in medical costs. This study primarily applied descriptive analysis and a generalized linear model with a gamma distribution and a log link. Results In total, 92,856 lung cancer patients with inpatient records were identified, with Renminbi (RMB) 11,276 [6322-20,850] (median [interquartile range]) medical costs for the UEBMI group and RMB 8303 [4492-14,823] for the URBMI group. Out-of-pocket (OOP) expenses for the UEBMI group was RMB 2143 [1108-4506] and RMB 2975 [1367-6275] for the URBMI group. The UEBMI group also had significantly higher drug costs, medical service costs, and medical consumable costs, compared to the URBMI group. Regarding city-specific insurances, medical costs for the UEBMI and the URBMI lung cancer patients in Shanghai were RMB 9771 [5183-16,623] and RMB 9741 [5924-16,067], respectively. In Xianyang, the medical costs for UEBMI and URBMI patients were RMB 11,398 [6880-20,648] and RMB 9853 [5370-24,674], respectively. The regression results showed that the UEBMI group had 27.31% fewer OOP expenses than the URBMI group did, while patients in Xiangyang and Xianyang had 39.53 and 35.53% fewer OOP expenses, respectively, compared to patients in Shanghai. Conclusions Compared with the URBMI patients, the UEBMI lung cancer patients obtained more or even better health services and had reduced financial burden. The differences in insurances among cities were greater, compared to those among insurances within cities, and the differences in OOP expenses between cities were greater compared to those between UEBMI and URBMI. Our results called for further reform of China's fragmented insurance schemes.